2007
DOI: 10.1186/1471-2180-7-55
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen restriction increases the infective potential of Listeria monocytogenes in vitro in Caco-2 cells and in vivo in guinea pigs

Abstract: Background: Listeria monocytogenes has been implicated in several food borne outbreaks as well as sporadic cases of disease. Increased understanding of the biology of this organism is important in the prevention of food borne listeriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 26 publications
3
34
0
2
Order By: Relevance
“…The importance of the anaerobic environment is supported by data from Larsen et al (101), who reported higher invasion of Caco-2 cells by L. monocytogenes grown for 2 and 4 weeks on modified atmosphere-packaged ham at 4°C than by bacteria grown in BHIB. Andersen et al (102) reported that L. monocytogenes grown under oxygen-restricted conditions were more invasive to Caco-2 cells and yielded higher bacterial loads in organs after oral guinea pig challenge than did bacteria grown without oxygen restriction. In contrast to our findings, Olesen et al (20) reported that L. monocytogenes strain O57 prfA transcript levels were significantly higher in bacteria grown in BHI than in those grown in liver pâté at 7°C.…”
Section: Figmentioning
confidence: 99%
“…The importance of the anaerobic environment is supported by data from Larsen et al (101), who reported higher invasion of Caco-2 cells by L. monocytogenes grown for 2 and 4 weeks on modified atmosphere-packaged ham at 4°C than by bacteria grown in BHIB. Andersen et al (102) reported that L. monocytogenes grown under oxygen-restricted conditions were more invasive to Caco-2 cells and yielded higher bacterial loads in organs after oral guinea pig challenge than did bacteria grown without oxygen restriction. In contrast to our findings, Olesen et al (20) reported that L. monocytogenes strain O57 prfA transcript levels were significantly higher in bacteria grown in BHI than in those grown in liver pâté at 7°C.…”
Section: Figmentioning
confidence: 99%
“…monocytogenes ScottA, labeled with either CFP or YFP by Andersen et al (2006), 42 was used to investigate the impact of oxygen restriction on the infection potential. 43 Using a Caco-2 cell model system L. monocytogenes-CFP and L. monocytogenes-YFP, grown under oxygen restricted conditions were approximately 100-fold more invasive than corresponding cultures grown in the presence of oxygen. The oral infection of guinea pigs with mixtures (1:1 ratio) of oxygen restricted and unrestricted fluorescently labeled L. monocytogenes demonstrated that the oxygen restricted L. monocytogenes cells are significantly more invasive than their unrestricted counterparts, shown by the numbers of bacteria recovered from the liver, spleen and jejunum together with established fecal concentrations.…”
Section: Bioluminescent Imagining (Bli)mentioning
confidence: 99%
“…This study suggests that infective potential of L. monocytogenes in humans might also depend on oxygen levels encountered before ingestion, a concept that has obvious implications for food processors and packagers. 44 eGFP emits more intense light and with slightly different spectral properties when compared to GFP. eGFP based promoter reporters were utilized in a study of the SOS response in L. monocytogenes and this was presented by Stijn van der Veen genes under PrfA control appeared primarily in the blood.…”
Section: Bioluminescent Imagining (Bli)mentioning
confidence: 99%
“…Thiols, amines, aromatic residues, heme groups, and iron-sulfur clusters are particularly susceptible to attack by RNIs, making many key metabolic enzymes targets (17,18). UPEC may also encounter RNIs outside the urinary tract, possibly during passage through the upper gastrointestinal tract, where nitrate (NO 3 Ϫ ) and nitrite (NO 2 Ϫ ) levels can be very high, or on the surface of meat products, which are often treated with nitrite as a coloring agent and preservative (15,16,27,29,64).Adaptive responses that allow a bacterial population to survive one stressful condition can, in some instances, enhance its ability to handle other environmental stresses (2,5,31,32,42). This cross-protective effect may also potentiate bacterial virulence within a host.…”
mentioning
confidence: 99%
“…Adaptive responses that allow a bacterial population to survive one stressful condition can, in some instances, enhance its ability to handle other environmental stresses (2,5,31,32,42). This cross-protective effect may also potentiate bacterial virulence within a host.…”
mentioning
confidence: 99%